2021
DOI: 10.21608/jssae.2021.158665
|View full text |Cite
|
Sign up to set email alerts
|

Development a Locale Thresher Machine for Separating Peanut Crop

Abstract: A threshing process for peanut crop is considered one of the most essential agricultural operations. Therefore, the research aimed to develop a local threshing machine for separating and extracting the peanut pods from straw and other materials. This was done by replacing the normal concave with a new one with opening of 7×7cm per opening (square shape). The front sieve is replaced with its last holes in the form of slides, with a distance of 0.5 cm. And adjusting the clearance between the threshing drum and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Past studies have reported that the optimal selection of threshing rotational speed and the thresher-concave distance can increase the threshing Feeding rate, (kg•h -1 ) efficiency and also reduce the broken pod percentage simultaneously. These results are consistent with the results achieved in this study (Aboegela and Mourad, 2021;Senthilkumar et al, 2017;Srinivasan et al, 2021;Vennela et al, 2018).…”
Section: Figure 10 Impact Of the Feeding Rate On The Separation Ratesupporting
confidence: 94%
See 3 more Smart Citations
“…Past studies have reported that the optimal selection of threshing rotational speed and the thresher-concave distance can increase the threshing Feeding rate, (kg•h -1 ) efficiency and also reduce the broken pod percentage simultaneously. These results are consistent with the results achieved in this study (Aboegela and Mourad, 2021;Senthilkumar et al, 2017;Srinivasan et al, 2021;Vennela et al, 2018).…”
Section: Figure 10 Impact Of the Feeding Rate On The Separation Ratesupporting
confidence: 94%
“…According to initial experiments, it was found that at the rotational speed less than 50 rpm the tresher does not have a high ability to separate the seeds from the pod, although the percent of damaged seeds is low. According to previous studies, at a rotational speed greater than 100 rpm, threshers have a high ability to separate seeds from the pod, however the number of damaged seeds has also increased with increasing threshing speed (Aboegela and Mourad, 2021;Senthilkumar et al, 2017;Srinivasan et al, 2021;Vennela et al, 2018). Therefore, in this experiment, the thresher rotational speed was selected between 100 and 300 rpm to determine the optimal value of the thresher speed in combination with the feeding rate and the thresher-concave distance (Table 1).…”
Section: Figure 1 a Panut Threshing Machinementioning
confidence: 97%
See 2 more Smart Citations